Deconstructing 'the foreign': The limits of citizenship for explaining price competition in the Spaza sector in South Africa. Issue 5 (2nd September 2016) - Piper, Laurence; Yu, Derek
ABSTRACT: An important component of the informal economy in South Africa, the Spaza sector is portrayed as dominated by foreign nationals who outcompete South African shopkeepers on price. Indeed, this business competition from foreign nationals is a key reason given to explain xenophobia in South Africa. This article sets out to interrogate this widely held assumption. Drawing on evidence from over 1000 Spaza shops from South Africa's three main cities, the article makes the case that business competitiveness does not correspond with 'foreign' or South African identities in a simple way. Firstly, while citizenship or nationality is a factor, it is not captured by the labels of 'foreign' versus South African, as there are significant differences by nationality within the 'foreign'. Secondly, not all foreign nationalities out-compete South Africans on price. Thirdly, place matters too, not only because we find different nationalities in different cities, but also because there are different patterns of price competition by nationality in each place. Lastly, there are product-specific dynamics that impact on price more profoundly than nationality. For example, regardless of nationality, milk is cheaper in Cape Town and bread is cheaper in Johannesburg.